Fretting fatigue crack propagation rate under variable loading conditions - C. Gandiolle; S. Fouvry (Fracture and Structural Integrity)
Fretting fatigue experiments aim to represent industrial problems and most of them endure variable loading. Being able to assess lifetime of assemblies, especially for low propagation rate conditions, is essential as experimental validation is often too expensive. Both experimental and numerical approaches are proposed to follow the crack propagation rate of steel on steel cylinder/plane fretting fatigue contact submitted to variable loading conditions. An original experimental monitoring has been implemented on the fretting-fatigue test device to observe crack propagation using a potential drop technique. A calibration curve relating crack length and electrical potential was established for the studied contact. It allows direct knowledge of the crack length and crack propagation rate. It was applied to mixed load test showing crack arrest for the last loading condition. To explain this behavior, a 2-dimensional FE modeling was implemented to simulate the complexes multi-axial contact stressing. The crack propagation rate was formalized using an effective stress intensity factor amplitude ?Keff coupled with Paris law of the material. The crack arrest condition for a given loading was related to ?Keff along the expected crack path crossing the material crack arrest threshold ?K0. The failure was related to ?Keff reaching the critical stress intensity factor KIC. A good correlation with experiments was observed allowing to predict the crack arrest condition although the model tends to overestimate the final crack length extension.